Jaundice - Method of diagnosing and treating its causes - Martin, Lay (1942)
In this work I have tried to make a recapitulation of biliary secretion physiology. More detailled descriptions, as much as references, may be found in Rich (3), Mann (25). Barrón (5) and the author' s (29) articles. Only through a deep knowledge of the matter, is possible to go on in the knowledge of the different cases of jaundice. In front of an established jaundice case, it is possible to place the origin of the sickness in a high percentage of cases with the help of the history, the physical examination and the different tests. When the diagnosis is already made the therapy may be instituted specific, of maintenance or surgical. There will be many cases in which the diagnosis will stay without resolution. In these cases, most import decision is the selection of a medical or surgical treatment. It is impossible to give exact rules for selecting the proceeding, not with standing several principles may be suggested. In the youth and the early adult's life, the hepatic pathology is generally a hepatitis for which surgery offers no solution. Further, the importance of surgery is of first order. If a stone of the common duct is permitted to obstruct it during a too long period it would cause the destruction of the hepatic cells. In cases of malignant growth of the head of the pancreas, surgery is not only a palliative, but also is of great value to prolong a life in a more comfortable way. After the middle-age, when the diagnosis oscillates between an obstruction and an hepatitis (infections generally), surgery is indicated after a fitted observation period. Lives may be saved and if the development of the cases proves to be of the medical type it shall have been done very little harm, particularly if a fitted pre-operatory preparation have been given, and if the selection of an anesthetic is restrained to those which are not toxic for the lives.